Chemistry Evolves, Terms Evolve, but Phenomena Do Not Evolve: From Chalcogen–Chalcogen Interactions to Chalcogen Bonding. Issue 50 (24th September 2020) - Kolb, Simon; Oliver, Gwyndaf A.; Werz, Daniel B.
Abstract: Chalcogen bonding is important in numerous aspects of chemistry, both in the solid state and in solution. Surveying the literature, it becomes clear that during its rebranding from chalcogen–chalcogen interactions, some parts of the community have somewhat neglected to recall its discovery and the initial studies referring to it in its previous guise. In this Viewpoint, we trace the path of research into this phenomenon, from its discovery, through its renaming, and to some of the varied and interesting chemistry it has led to so far, ranging from crystal engineering through supramolecular assembly to modern catalysis. Abstract : Chalcogen bonding describes the interaction of Lewis‐acidic chalcogen atoms with a variety of Lewis‐basic atoms. This Viewpoint assesses the development of this term from its predecessor "chalcogen–chalcogen interactions" through discussion of some of the varied and fascinating chemistry it has inspired.